2009
DOI: 10.1073/pnas.0903614106
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of substrate selection by the N-end rule adaptor protein ClpS

Abstract: The N-end rule is a conserved degradation pathway that relates the stability of a protein to its N-terminal amino acid. Here, we present crystal structures of ClpS, the bacterial N-end rule adaptor, alone and engaged with peptides containing N-terminal phenylalanine, leucine, and tryptophan. These structures, together with a previous structure of ClpS bound to an N-terminal tyrosine, illustrate the molecular basis of recognition of the complete set of primary N-end rule amino acids. In each case, the ␣-amino g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 31 publications
5
69
0
Order By: Relevance
“…Short peptides with leucine or phenylalanine at the N terminus were effective inhibitors of LR-GFP Venus degradation, but the presence of a single hydrophilic residue at the N terminus of the peptides rendered them completely ineffective as inhibitors. These data are consistent with other studies showing that ClpS is needed to mediate degradation of proteins targeted by virtue of an N-degron (5,11,12,16).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Short peptides with leucine or phenylalanine at the N terminus were effective inhibitors of LR-GFP Venus degradation, but the presence of a single hydrophilic residue at the N terminus of the peptides rendered them completely ineffective as inhibitors. These data are consistent with other studies showing that ClpS is needed to mediate degradation of proteins targeted by virtue of an N-degron (5,11,12,16).…”
Section: Discussionsupporting
confidence: 82%
“…ClpS binds a single molecule of N-end rule substrate (12,16). To test whether the efficiency of substrate delivery was dependent on the number of ClpS bound to ClpA 6 , we measured degradation as a function of LR-GFP Venus concentration with different stoichiometric ratios of ClpS to ClpA 6 .…”
Section: Maximum Degradation Of N-end Rule Proteins Occurs With One Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-domain contains a hydrophobic binding pocket, whereas the UBR box uses several negatively charged side chains in binding pockets. [11][12][13] In a previous study, we confirmed that the L-conformation, protonated a-amine group, and hydrophobic side chains are essential N-degron structural components required for direct interaction with N-recognins. 14 Based on this conformational information, several small, biocompatible Arg/N-end rule inhibitors have been developed to target both the UBR box and the N-domain simultaneously.…”
Section: Introductionmentioning
confidence: 59%
“…Another adapter, RssB, specifically targets the factor RpoS for degradation by ClpXP (14 -16). ClpA on the other hand interacts with the adapter ClpS, which binds proteins bearing one of a small subset of N-terminal residues and delivers them to ClpAP for degradation (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%